Hedonic Consumption in Times of Stress: Reaping the Emotional Benefits Without the Self-Regulatory Cost - Balleyer, Anna H.; Fennis, Bob M. (Frontiers in Psychology, 2022)
Hedonic consumption is pleasant but can interfere with the capacity to self-regulate. In stressful moments, when self-regulation is arguably still important, individuals often indulge in hedonic consumption. In two experiments, we investigate whether hedonic consumption negatively affects self-regulation under moderately stressful conditions and whether selecting hedonic consumption under moderately stressful conditions is driven by high or low self-control. In both studies, participants were randomly exposed to a mental arithmetic task that was either completed under time pressure with performance feedback (moderate stress) or without time pressure and without feedback (no stress). Experiment 1 assigned participants to a hedonic (vs. neutral) consumption task and then measured impulse control via a color-word Stroop task. Experiment 2 measured self-control as a second independent variable and recorded hedonic (vs. neutral) consumption. The results show that moderate stress buffered the negative effect that hedonic consumption has on self-regulation under no stress conditions and that high rather than low self-control predicts hedonic over neutral consumption under stress. These findings indicate that hedonic consumption in response to moderate stress may be a strategic choice to reap the pleasure benefit of hedonic consumption while the costs to self-regulation are low.